Nanocellulose : from nature to high performance tailored materials - Dufresne, Alain, 1962- (De Gruyter, 2012)
This specialist monograph provides an overview of the recent research on the fundamental and applied properties of nanoparticles extracted from cellulose, the most abundant polymer on the planet and an essential renewable resource. The author pioneered the use of cellulose nanoparticles (cellulose nanocrystals or whiskers and cellulose microfibrils) in nanocomposite applications. The book combines a general introduction to cellulose and basic techniques with more advanced chapters on specific properties and applications of nanocellulose.
Keywords: Cellulose -- Chemistry.; Cellulose nanocrystals.; Cellulose -- Mechanical properties.; elektronické knihy; electronic books